Development of a tool for reporting environmental infractions and crimes: "Sou Eco" - Costa, Isaque Vilson Batista; Freitas, Lohan V. S.; Cardoso, Evaldo P. S.; Cardoso, Fábio de Sousa; Printes, Andre Luiz; Gomes, Raimundo Cláudio Souza; Torné, Israel Gondres; Azevedo, Vitor Norton Lima; Monteiro, Gabriella Rabelo; Cisneros, Edry Antonio Garcia (Seven Editora, 2023)
This project provides an application for performing, checking and managing environmental complaints. The system is built on three platforms: a web application for the management of complaints, intended for the bodies responsible for environmental inspection to monitor the complaints made to the whistleblowers; and the mobile application, both for Android and iOS, intended for the population to perform complaints in urban and rural locations. The three systems are available in partnership with the State Court of Auditors (SCA). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-163